Introduction to the Science Popularization Industry - Ren, Fujun. author. aut Link
XXIV, 331 p. 33 illus., 8 illus. in color.
Keywords: This book systematically introduces the popular science industry. It firstly summarizes the social basis and research status of the development of contemporary science popularization industry and also elaborates on the basic theory and main forms of science popularization industry. The most important feature of this book is its focus on the practice and case study of the development of science popularization industry in China. Meanwhile, it analyzes the development of science popularization industry in China from four perspectives: the basis and conditions, the current situation and countermeasures, the main promotion tasks, and the policy suggestions for promotion. The book analyzes the development trend of science popularization industry in China. It can be used as a reference book for science popularization practitioners and enthusiast to learn and understand the theory and practice of science popularization industry. It can also be used as a textbook for the cultivation and training of science popularization talents.